2021
DOI: 10.1016/j.ajog.2021.04.232
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of fetal growth and elevated maternal serum sFLT1:PlGF are associated with early term spontaneous labor

Abstract: Background The physiological control of human parturition at term is unknown. Objective This study aimed to test the hypothesis that slowing of fetal growth or elevated maternal serum levels of markers of placental hypoxia in late gestation will be associated with earlier term labor. Study Design We observed 2208 women having first births and performed serial blinded ultrasonography and immunoassay of soluble fms-like tyrosine kinase-1 and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…When the syncytiotrophoblast experiences lower oxygen supply and as it becomes hypoxic, more sFlt-1 is shed into the maternal circulation [ 82 ]. It was shown that PlGF, sFlt-1 and the sFlt-1/PlGF ratio were associated with spontaneous delivery [ 83 , 84 ]. Therefore, the associations between the angiogenetic biomarkers may play a role as a pregnancy biologic clock.…”
Section: Discussionmentioning
confidence: 99%
“…When the syncytiotrophoblast experiences lower oxygen supply and as it becomes hypoxic, more sFlt-1 is shed into the maternal circulation [ 82 ]. It was shown that PlGF, sFlt-1 and the sFlt-1/PlGF ratio were associated with spontaneous delivery [ 83 , 84 ]. Therefore, the associations between the angiogenetic biomarkers may play a role as a pregnancy biologic clock.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,26 Finally, preterm labour is associated with an anti-angiogenic profile of an elevated sFlt-1-to-PlGF ratio, in common with PE and FGR. 10,11 The ASPRE trial did not find a significant difference in sPTB in the aspirin vs the placebo group. 12 Nevertheless, the results of an individual participant data meta-analysis including 17 RCT and 28,797 women showed a lower risk of sPTB at less than 37 weeks (RR 0.93, 95% CI 0.86-0.996) and less than 34 weeks (RR 0.86, 95% CI 0.76-0.99) in women assigned to antiplatelet treatment compared with placebo or no treatment.…”
Section: Women Who Delivered Spontaneously Preterm Had Lower Papp-a M...mentioning
confidence: 98%
“…Furthermore, approximately one-third of patients with sPTB have a failure of physiological transformation of the myometrial segments of the spiral arteries, which is typically associated with PE and FGR 8,9,26 . Finally, preterm labor is associated with an antiangiogenic profile of an elevated ratio of sFlt-1 to PlGF, in common with PE and FGR 10,11 .…”
Section: Interpretation Of Study Findings and Comparison With Publish...mentioning
confidence: 99%
See 2 more Smart Citations